The Effect of Fun Cooking Activities on the Creative Thinking Skills of 5-6 Year Old Children at DWP Kemanggen Kindergarten - Suryaningsih, Della Aulia; Widayanti, Melia Dwi; Malaikosa, Yes Matheos Lasarus; Maulidiyah, Eka Cahya; Ningrum, Mallevi Agustin (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This research was motivated by the low creative thinking skills of children at DWP Kemangsen Kindergarten. The purpose of this study was to examine the effect of implementing fun cooking activities on the creative thinking skills of children aged 5-6 years at DWP Kemangsen Kindergarten. This study used a quantitative experimental approach with a Quasi-Experimental Design with a Non-Equivalent Control Group Design. The sample and population in this study were all children aged 5-6 years at DWP Kemangsen Kindergarten, divided into two classes, each with 20 children. The data collection technique used was an observation sheet. The collected data consisted of pre-test and post-test scores from the control group and the experimental group, which received treatment through fun cooking activities in three sessions, each with a different fun cooking activity. The data were then analyzed and hypothesis tested using a Paired Sample T-Test. The analysis results showed a significance value <0.001, with a Sig. value of 0.001 less than 0.005, therefore, H0 was rejected and Ha was accepted. This indicates a significant change in the experimental group. The most significant improvement was in the fluency indicator, which is the child's ability to ask and answer many questions during the learning process. By rejecting H0 and accepting Ha, it can be concluded that the fun cooking treatment has an effect on the creative thinking skills of 5-6 year old children at DWP Kemangsen Kindergarten